2022
DOI: 10.3390/polym14163400
|View full text |Cite
|
Sign up to set email alerts
|

Dry-Matter Loss and Changes in the Chemical Composition of Spruce Wood after Long-Term Storing in the Form of Roundwood

Abstract: Wood stock in a warehouse is a necessary precondition for reliable manufacturing. However, wood can degrade and lose the matter during storage. “Dry-matter loss (DML)” is used to quantify the degradation following the changes in weight of a wood substance. The proposed calculation of DML is based on using parallel figures. The calculated loss of spruce wood substance harvested in winter during a six-month period was 4.5%. The estimated annual loss of wood substance was 5.7%. The loss was caused by a factor wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Dry matter loss was measured to determine the biomass degradation trend during the storage time. The sample was dry by using the oven at 105-degree Celsius and 24 hours before the calculation of dry matter loss (Afzal et al, 2010;Hrčka et al, 2022), as shown in Eq. 1.…”
Section: Sampling Technique and Parameters Studiedmentioning
confidence: 99%
“…Dry matter loss was measured to determine the biomass degradation trend during the storage time. The sample was dry by using the oven at 105-degree Celsius and 24 hours before the calculation of dry matter loss (Afzal et al, 2010;Hrčka et al, 2022), as shown in Eq. 1.…”
Section: Sampling Technique and Parameters Studiedmentioning
confidence: 99%